2019
DOI: 10.1186/s12866-019-1676-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Listeria monocytogenes strains in ruminant abortion and rhombencephalitis cases in comparison with the natural environment

Abstract: BackgroundListeria monocytogenes is the causative agent of listeriosis, a serious disease affecting both animals and humans. Here, multilocus sequence typing (MLST) was used to characterize the genetic diversity of Listeria monocytogenes strains isolated from the natural environment and animal clinical cases in Europe. The prevalence of clonal complexes (CCs) obtained was compared according to (i) the origin of isolation – clinical cases vs. natural environment – and (ii) the clinical form of animal listeriosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(84 citation statements)
references
References 46 publications
10
66
0
8
Order By: Relevance
“…Two further strains (8%) were assigned to CC6, which is an emerging epidemic L. monocytogenes serotype 4b clone causing major outbreaks and severe forms of human listerial meningitis worldwide 6 , 24 . Other CCs identified among the strains in this study included L. monocytogenes serotype 1/2a CC7, CC11 and CC29, all of which have been associated with outbreaks occurring in the US between 1987 and 2011, and further found to represent environmental strains that persist within food production and livestock environments globally 23 , 25 27 . On the other hand, L. monocytogenes serotype 1/2a CC37 found in two samples in this study, is associated with abortion in small ruminants and cattle and found frequently in wildlife and ruminant environments 13 , 25 , 28 .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Two further strains (8%) were assigned to CC6, which is an emerging epidemic L. monocytogenes serotype 4b clone causing major outbreaks and severe forms of human listerial meningitis worldwide 6 , 24 . Other CCs identified among the strains in this study included L. monocytogenes serotype 1/2a CC7, CC11 and CC29, all of which have been associated with outbreaks occurring in the US between 1987 and 2011, and further found to represent environmental strains that persist within food production and livestock environments globally 23 , 25 27 . On the other hand, L. monocytogenes serotype 1/2a CC37 found in two samples in this study, is associated with abortion in small ruminants and cattle and found frequently in wildlife and ruminant environments 13 , 25 , 28 .…”
Section: Resultsmentioning
confidence: 87%
“…Other CCs identified among the strains in this study included L. monocytogenes serotype 1/2a CC7, CC11 and CC29, all of which have been associated with outbreaks occurring in the US between 1987 and 2011, and further found to represent environmental strains that persist within food production and livestock environments globally 23 , 25 27 . On the other hand, L. monocytogenes serotype 1/2a CC37 found in two samples in this study, is associated with abortion in small ruminants and cattle and found frequently in wildlife and ruminant environments 13 , 25 , 28 . Further, L. monocytogenes CC37 is prominent in milk samples from US dairy farms 29 .…”
Section: Resultsmentioning
confidence: 87%
“…While L. monocytogenes is frequently found in animals, on farms, and in the natural environment, the frequency of the different genetic groups of L. monocytogenes appears to differ significantly in these environments compared to that observed in meat products and the meat processing industry. L. monocytogenes ST9 is rarely found in pig or ruminant farming environments, animals, or wild natural surroundings ( 22 , 58 60 ). This sequence type has, however, frequently been found to dominate in raw pork meat ( 21 , 52 , 61 ) and is also commonly found to persist in slaughterhouses ( 14 , 15 , 24 , 62 ) as well as in downstream compartments in the meat processing chain ( 10 , 22 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although increasing reports are available on the prevalence of Lm in diverse wild species [ 9 , 16 , 29 , 35 , 36 ], it is rare to isolate Lm strains from a dolphin. In England, systematic surveillance programs were conducted on 728 cetaceans of 16 different species tested for 12 consecutive years and no Lm strain was ever detected [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…CC121 strains pose a serious challenge to the food industry, as they are overrepresented in all food sectors [ 18 , 19 ], and can persist in different food processing plants for years [ 20 , 21 , 22 , 23 , 24 , 25 ]. Remarkably, in farming animals, CC121 strains are either never observed [ 26 , 27 , 28 , 29 ] or observed with a low prevalence [ 16 , 30 ]. Regarding wild mammals, only one study has reported the occurrence of CC121 strains among hedgehogs, in the UK [ 4 ].…”
Section: Introductionmentioning
confidence: 99%